Oral health status and treatment requirements of different residential homes in Istanbul: A comparative study - EVREN, BUKET; ÖZKAN, YASEMİN (ELSEVIER IRELAND LTD, 2011)
The purpose of this study was to investigate dental/denture status of the elderly people living in different residential homes. In 346 elderly people from different residential homes two belonging to the state (Group 1 and Group 2) and one supported by private foundations (Group 3) were examined. Sixty percent of participants were edentulous and 22.8% of participants had no complete dentures which 9 (7.4%) of them were in Groups 1 and 2. Over 50% of the participants had no or low income and 45% of participants were illiterate. All of the participants who were illiterate and had low income were in Group 1 and Group 2. Oral hygiene was good for 15.4% and only 19.4% of participants removed their dentures overnight. Denture stomatitis was observed in 61.7% of subjects. Significant correlation was found between denture hygiene and age of participant, general health status, denture stomatitis, and overnight denture wear (p = 0.001). The decayed, missing and filled teeth (DMFT) scores were 25.52 +/- 3.37. There was statistically significant differences between groups for DMFT scores (p = 0.016). Dental health education is also needed focusing on the special needs of this neglected and socioeconomically deprived population to improve their quality of life. (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: Oral and dental health; Edentulism; Edentulousness; Institutionalized elderly; HYGIENE HABITS; ADULTS; CLEANLINESS; EDENTULISM; PEOPLE; STOMATITIS; DENTURES; SERVICES; YEASTS